2006
DOI: 10.1016/j.amjhyper.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Muscle Metaboreflex Control of Sympathetic Activity in Never-Treated Hypertensive Subjects

Abstract: These findings suggest an association between hypertension and decreased muscle metaboreflex control of MSNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
4
24

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 24 publications
1
59
4
24
Order By: Relevance
“…24 The increase in diastolic blood pressure after water ingestion found in hypertensive and normotensive subjects was similar to that observed in patients with multiple system atrophy and pure autonomic failure with sympathetic denervation. 1 In agreement with previous observations, 25 our subjects with mild hypertension showed higher baseline MSNA when compared to normotensive subjects. However, forearm vascular resistance, parasympathetic nervous activity and spontaneous baroreflex sensitivity at baseline of our mildly hypertensive subjects were similar to normotensive individuals.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…24 The increase in diastolic blood pressure after water ingestion found in hypertensive and normotensive subjects was similar to that observed in patients with multiple system atrophy and pure autonomic failure with sympathetic denervation. 1 In agreement with previous observations, 25 our subjects with mild hypertension showed higher baseline MSNA when compared to normotensive subjects. However, forearm vascular resistance, parasympathetic nervous activity and spontaneous baroreflex sensitivity at baseline of our mildly hypertensive subjects were similar to normotensive individuals.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have shown that arterial hypertension is accompanied by an increased forearm vascular resistance, impairment of the baroreflex regulation, and reduced parasympathetic modulations to the sinus node. [25][26][27] However, it is possible that the group of hypertensive patients in our study could be at an early stage of their natural history, before these haemodynamic and autonomic changes are apparent. .…”
Section: Discussionmentioning
confidence: 95%
“…After the maximum voluntary contraction (MVC; average of three trials) was obtained, handgrip isometric exercise was performed at 30% of MVC with the dominant arm using a handgrip dynamometer. It has been shown that this strategy causes substantial nonexercise muscle vasodilatation in humans (1,25,30). Handgrip isometric exercise has been used to assess vascular function in adults and children (2,24,30).…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…Blood pressure was monitored noninvasively and intermittently with an automatic and oscillometric cuff (Dixtal, DX 2710; Manaus, Brazil) placed on the ankle with a cuff width adjusted to ankle circumference (24,29). The cuff inflated every 30 s. Heart rate was monitored continuously through lead II of EKG.…”
Section: Measurements and Proceduresmentioning
confidence: 99%
“…After the maximum voluntary contraction (MVC; average of three trials) was obtained, handgrip isometric exercise was performed at 30% of MVC with the dominant arm using a handgrip dynamometer. It has been shown that this strategy causes substantial nonexercise muscle vasodilatation in humans (3,29,35). The individuals were instructed to breath normally during exercise and to avoid inadvertent performance of Valsalva maneuver.…”
Section: Measurements and Proceduresmentioning
confidence: 99%